Teaching social justice critical tools for the intercultural communication classroom - Lawless, Brandi 1985-; Chen, Yea-Wen (Rowman & Littlefield, 2021)
"This pedagogical guide presents conceptual overviews, student activities, and problem-solving strategies for teaching intercultural communication. The authors navigate eight categories of potential conflict, including: communicating power and privilege, engagement in social justice, and assessing intercultural pedagogies for social justice"--